Airborne PM2.5 pollution: A double-edged sword modulating hepatic lipid metabolism in middle-aged male mice. (1st May 2023) - Hu, Renjie; Zhang, Lu; Qin, Li; Ding, Hao; Li, Ran; Gu, Weijia; Chen, Rucheng; Zhang, Yunhui; Rajagoplan, Sanjay; Zhang, Kezhong; Sun, Qinghua; Liu, Cuiqing
Abstract: Emerging evidence suggests that exposure to airborne fine particulate matter (PM2.5 ) is closely related to disturbances in hepatic lipid metabolism. However, no systematic study assessed the age vulnerability in effects of PM2.5 exposure on metabolism, and the potential mechanisms remain unknown. This study aimed to investigate the metabolic susceptibility of different life stages to PM2.5 exposure, and to evaluate the underlying molecular mechanisms. Male C57BL/6 mice at three life phases (young, adult, and middle-aged) were exposed simultaneously to concentrated ambient PM2.5 or filtered air (FA) for 8 weeks using a whole-body inhalational exposure system. The average daily PM2.5 concentrations to which mice were actually exposed were 90.71 ± 7.99 μg/m 3 . The body weight, total food utilization, body composition, glucose metabolic homeostasis of the mice were evaluated. At euthanasia, serum and liver samples were collected to measure lipid profiles and hepatic function. H&E and Oil Red O staining were used to assess the liver cellular structure and hepatic lipid deposition. Transcriptomics and lipidomics were performed to determine the differentially expressed genes and lipid metabolites in the liver. Quantitative RT-PCR and immunoblots were performed to verify the transcriptomics and explore the mechanism for metabolic susceptibility. PM2.5 exposure led to reductions in body weight gain, total food utilization, and fat mass in middle-aged mice but not in young or adults. Exposure to PM2.5 reduced hepatic lipid deposition by enhancing lipolysis and inhibiting the glycerol-3-phosphate (G3P) pathway of hepatic lipogenesis. Furthermore, PM2.5 exposure attenuated hepatic fatty acid metabolism and primary bile acid biosynthesis. Finally, PM2.5 exposure dysregulated hepatic phospholipid metabolism, as evidenced by increased glycerophospholipid synthesis and disturbed sphingolipid metabolism. Therefore, middle-aged male mice were more vulnerable to PM2.5 exposure with double-edged effects, improved metabolism and hepatic TG accumulation but inhibited hepatic fatty acid and bile acid metabolism and dysregulated phospholipid metabolism. Graphical abstract: Image 1 Highlights: Middle-aged male mice were more vulnerable to PM2.5 exposure. PM2.5 exposure had double-edged effects on metabolism of middle-aged mice. PM2.5 exposure reduced hepatic TG deposition in middle-aged mice. PM2.5 exposure inhibited hepatic FA and bile acid metabolism in middle-aged mice. PM2.5 exposure dysregulated hepatic phospholipid metabolism in middle-aged mice.